On generalized ω-closed sets - Khalid Y. Al-Zoubi (International Journal of Mathematics and Mathematical Sciences)
The class of ω-closed subsets of a space (X,τ) was defined to introduce ω-closed functions. The aim of this paper is to introduce and study the class of gω-closed sets. This class of sets is finer than g-closed sets and ω-closed sets. We study the fundamental properties of this class of sets. In the space (X,τω), the concepts closed set, g-closed set, and gω-closed set coincide. Further, we introduce and study gω-continuous and gω-irresolute functions.